Multilingual email zoning - Jardim, Bruno (2022)
Jardim, B., Rei, R., & Almeida, M. S. C. (2021). Multilingual email zoning. In EACL 2021 - 16th Conference of the European Chapter of the Association for Computational Linguistics, Proceedings of the Student Research Workshop (pp. 88-95). (EACL 2021 - 16th Conference of the European Chapter of the Association for Computational Linguistics, Proceedings of the Student Research Workshop). Association for Computational Linguistics (ACL). --------------------------- Funding Information: This project has received funding from the European Union's Horizon 2020 research and innovation program under grant agreement No 873904. Funding Information: This project has received funding from the European Union’s Horizon 2020 research and innovation program under grant agreement No 873904. Publisher Copyright: © 2021 Association for Computational Linguistics